Evaluation of apps and design of a technological resource for learning music - León-Garrido, Antonio; Barroso-Osuna, Julio Manuel (Texto Livre, 2025)
The constant growth of mobile apps and their integration into education have raised questions about quality and suitability for educational contexts. In this study, mobile apps aimed at learning music education were evaluated using a specific evaluation instrument. Additionally, possible differences between experts in educational technology and music, compared to those specialised only in music, were analysed. Sixty teachers specialising in music education participated, of whom 28 belonged to university institutions and 32 to primary education centres. The results showed a high rate of agreement in the evaluations (CCI = 0.957) and a weighted average of 3.5 out of 5 points for the apps analysed. Furthermore, no statistically significant differences were found between the evaluation groups, suggesting consistency in the endpoints. These findings highlight the importance of evaluating and developing educational mobile apps based on defined and education-orientated quality criteria. For these reasons, we conclude by proposing a new mobile app that integrates the quality characteristics identified in the analysis. This new app represents a significant contribution to the teaching of music, contributing to improving educational results through the use of technology, and promoting learning in a significant way.